2006
DOI: 10.1002/cncr.21989
|View full text |Cite
|
Sign up to set email alerts
|

Final results of the Canadian prospective phase II trial of intermittent androgen suppression for men in biochemical recurrence after radiotherapy for locally advanced prostate cancer

Abstract: The impact of reduced‐intensity conditioning (RIC) on the outcomes of hematopoietic cell transplantation (HCT) from unrelated ‐donors (UD) remains to be determined. We therefore assessed 128 patients, aged 16 to 66 years, with acute leukemia (n = 105) or myelodysplastic syndrome (n = 23) in a UD‐HCT trial using RIC with busulfan, fludarabine, and antithymocyte globulin. Patients were transplanted with unmanipulated bone marrow (BM, n = 41) or mobilized peripheral blood mononuclear cells (M‐PB, n = 87) and rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 97 publications
(136 citation statements)
references
References 32 publications
2
118
1
Order By: Relevance
“…In figure 5a,b, the mean length of the off-treatment periods decreases with each succeeding cycle. This trend can be found in the clinical data (Bruchovsky et al 2006). However, the trend is not applicable to the case when the initial testosterone level is relatively high as shown in figure 5c.…”
Section: (C) Numerical Simulationsmentioning
confidence: 82%
See 4 more Smart Citations
“…In figure 5a,b, the mean length of the off-treatment periods decreases with each succeeding cycle. This trend can be found in the clinical data (Bruchovsky et al 2006). However, the trend is not applicable to the case when the initial testosterone level is relatively high as shown in figure 5c.…”
Section: (C) Numerical Simulationsmentioning
confidence: 82%
“…After reviewing mathematical modelling of IAS for prostate cancer, we have presented a stochastic model and shown that it is successful in reproducing statistical features of the time course of serum PSA in clinical trials (Bruchovsky et al 2006(Bruchovsky et al , 2007, such as the shortening of the off-treatment periods with more on-and off-treatment cycles and the inverse relationship between the serum PSA nadir level and the length of the off-treatment interval. However, the stochastic model is not able to replicate the biphasic decrease of the serum PSA level.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations